2021
DOI: 10.1136/bmjoq-2020-001061
|View full text |Cite
|
Sign up to set email alerts
|

Quality of rheumatology care for patients with fibromyalgia and chronic pain syndromes

Abstract: BackgroundOne-third of primary care providers (PCPs) refer patients with fibromyalgia or chronic pain (FM/CP) to specialist care, typically rheumatology. Yet, comprehensive data on the quality of rheumatology care for patients with FM/CP are currently lacking.MethodsRecords of patients referred for rheumatology consultation for FM/CP and seen at a single academic centre between 2017 and 2018 were extracted by retrospective chart review. Variables were diagnostic accuracy (at referral vs consultation), resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Rheumatologists have traditionally ‘owned’ fibromyalgia [ 61 ]. Yet, some are reluctant to accept patients with fibromyalgia for care [ 17 , 62 ] and the argument for diagnosis and treatment of people with fibromyalgia outwith rheumatology services is growing [ 61 , 63 ]. UK national audits show rheumatology services face challenges meeting quality standards for people with early inflammatory arthritis [ 64 , 65 ] and recent guidance published by the national Getting It Right First Time (GIRFT) programme [ 66 ] recommends that care for people with fibromyalgia should be provided in primary and community settings.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatologists have traditionally ‘owned’ fibromyalgia [ 61 ]. Yet, some are reluctant to accept patients with fibromyalgia for care [ 17 , 62 ] and the argument for diagnosis and treatment of people with fibromyalgia outwith rheumatology services is growing [ 61 , 63 ]. UK national audits show rheumatology services face challenges meeting quality standards for people with early inflammatory arthritis [ 64 , 65 ] and recent guidance published by the national Getting It Right First Time (GIRFT) programme [ 66 ] recommends that care for people with fibromyalgia should be provided in primary and community settings.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic errors may also be due to incomplete anamnesis caused by miscommunication. It has been found that up to 59% of the patients with chronic pain think they had difficulty in conveying their symptoms ( 224 ), which is not surprising considering the clinical complexity of this condition. Gathering a cPNL-based anamnesis may improve this situation.…”
Section: Implications For Chronic Pain Managementmentioning
confidence: 98%
“…For example, the thoracic outlet syndrome, which produces abundant signs and symptoms in the hand, may not belong to the scope of upper extremity surgeons, but, depending on the clinical institution, may be managed by neurosurgeons, thoracic surgeons, or vascular surgeons. In this regard, the specialized treatment of general chronic pain is even more problematic, because this condition is mostly managed by primary care providers ( 224 , 225 ) who have little experience in peripheral nerve diagnostics and treatment. Obviously, primary care doctors are aware to consult a large spectrum of relevant specialists.…”
Section: Implications For Chronic Pain Managementmentioning
confidence: 99%